Testing monotonicity of pricing Kernels - Yuri Golubev; Wolfgang Karl Härdle; Roman Timofeev (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
The behaviour of market agents has always been extensively covered in the literature. Risk averse behaviour, described by von Neumann and Morgenstern (1944) via a concave utility function, is considered to be a cornerstone of classical economics. Agents prefer a fixed profit over uncertain choice with the same expected value, however lately there has been a lot of discussion about the reliability of this approach. Some authors have shown that there is a reference point where market utility functions are convex. In this paper we have constructed a test to verify uncertainty about the concavity of agents' utility function by testing the monotonicity of empirical pricing kernels (EPKs). A monotone decreasing EPK corresponds to a concave utility function while non-monotone decreasing EPK means non-averse pattern on one or more intervals of the utility function. We investigated the EPK for German DAX data for years 2000, 2002 and 2004 and found the evidence of non-concave utility functions: H0 hypothesis of monotone decreasing pricing kernel was rejected at 5% and 10% significance level in 2002 and at 10% significance level in 2000.
Keywords: G12; C12; 330; Risk Aversion; Pricing kernel; Risikoaversion; Präferenztheorie; Börsenkurs; Aktienindex; Anlageverhalten; Theorie; Deutschland